2021
DOI: 10.3390/ijerph18189481
|View full text |Cite
|
Sign up to set email alerts
|

Public Protests and the Risk of Novel Coronavirus Disease Hospitalizations: A County-Level Analysis from California

Abstract: The objective of this study was to assess the relationship between public protests and county-level, novel coronavirus disease (COVID-19) hospitalization rates across California. Publicly available data were included in the analysis from 55 of 58 California state counties (29 March–14 October 2020). Mixed-effects negative binomial regression models were used to examine the relationship between daily county-level COVID-19 hospitalizations and two main exposure variables: any vs. no protests and 1 or >1 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Our findings are aligned with the findings by Moreno-Montoya et al ( 6 ) and Valentine et al ( 5 ), which describe a positive growth in the occurrence of COVID-19 cases after the protests; but were contrary to those of Neyman et al ( 4 ), which indicated that each individual protestor did not significantly contribute to the COVID-19 case rate in affected countries. Nor did our findings align with previous studies by Bui et al ( 19 )—which did not reveal a significant relationship between protests and COVID-19 hospitalization rates within California counties. Some possible explanations for these disparities may include a greater neglect of social distancing guidelines experienced during the dissents in Colombia, failure to use personal protective equipment, inadequate ventilation among areas shared by the large groups, the lower vaccination rate within this city: (720,325), which corresponds to 32% of the total population ( Figure 1C ) and the high rate of transmissibility of SARS-CoV-2, which has been associated with the ability of this virus to replicate extensively in bronchial and alveolar epithelia, the high “silent” presymptomatic transmission ( 20 ) and the reproductive number R0 (average number of secondary cases generated per typical infectious case), which for SARS-CoV-2 present a median point estimate of 3.1 ( 21 ).…”
Section: Discussioncontrasting
confidence: 61%
“…Our findings are aligned with the findings by Moreno-Montoya et al ( 6 ) and Valentine et al ( 5 ), which describe a positive growth in the occurrence of COVID-19 cases after the protests; but were contrary to those of Neyman et al ( 4 ), which indicated that each individual protestor did not significantly contribute to the COVID-19 case rate in affected countries. Nor did our findings align with previous studies by Bui et al ( 19 )—which did not reveal a significant relationship between protests and COVID-19 hospitalization rates within California counties. Some possible explanations for these disparities may include a greater neglect of social distancing guidelines experienced during the dissents in Colombia, failure to use personal protective equipment, inadequate ventilation among areas shared by the large groups, the lower vaccination rate within this city: (720,325), which corresponds to 32% of the total population ( Figure 1C ) and the high rate of transmissibility of SARS-CoV-2, which has been associated with the ability of this virus to replicate extensively in bronchial and alveolar epithelia, the high “silent” presymptomatic transmission ( 20 ) and the reproductive number R0 (average number of secondary cases generated per typical infectious case), which for SARS-CoV-2 present a median point estimate of 3.1 ( 21 ).…”
Section: Discussioncontrasting
confidence: 61%
“…Moreover, these acts of barbarity against protesters happened despite the protests being relatively peaceful with little loss to property (Beals 2020;Chenoweth and Pressman 2020;Human Rights Watch 2020;Singhvi 2020;Best 2023). Furthermore, the Black Lives Matter protests were safe as they did not cause an increase in COVID-19 transmission (Dave et al 2020;Bui et al 2021).…”
Section: The Logics Of Parasitism and Antiblacknessmentioning
confidence: 99%
“… 9. Some researchers have found a positive association between protests and COVID-19 case fatality rates (Zhai et al, 2021), while others have found no association at all (Bui et al, 2021; Moreno-Montoya et al, 2021; Neyman and Dalsey, 2021). …”
mentioning
confidence: 99%